2010
DOI: 10.1007/s00270-010-9895-x
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy of Bronchial Artery Aneurysm: Five Cases With Six Aneurysms

Abstract: The objective of this study was to investigate the effect of transcatheter arterial embolization (TAE) with N-butyl-2-cyanoacrylate (NBCA)-Lipiodol mixture in patients with bronchial artery aneurysm (BAA). From January 2005 to January 2010, five patients presenting hemoptysis with six BAAs were treated with NBCA-Lipiodol mixture, including intra-aneurysm embolization (IAE) in one patient. Adjuvant embolization with spherical polyvinyl alcohol (PVA) embolic microparticles or NBCA was first performed to embolize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…Previous reports described managing similar situation with N-butyl-2-cyanoacrylate (NBCA) [9,10]. In our case, catheter could reach the efferent artery but not to the fistula.…”
Section: Discussionsupporting
confidence: 45%
“…Previous reports described managing similar situation with N-butyl-2-cyanoacrylate (NBCA) [9,10]. In our case, catheter could reach the efferent artery but not to the fistula.…”
Section: Discussionsupporting
confidence: 45%
“…It has been suggested that both increased bronchial arterial flow and focal weakening of the vessel wall contribute to the pathogenesis of BAA. [2] Our analysis of the relevant literature revealed that BAA was most commonly associated with bronchiectasis (Fig. 6), with other factors being hypertension, chronic obstructive pulmonary disease vasculitis, chronic bronchopulmonary infection, tuberculosis, and trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptom of intrapulmonary BAA is hemoptysis, whereas mediastinal BAA presents with a variety of symptoms caused by compression of the adjacent structures, such as hemoptysis, dysphagia, hoarseness, superior vena cava syndrome, and severe chest pain mimicking acute aortic dissection caused by rupture (3,4). Therefore, the asymptomatic nature and incidental diagnosis of mediastinal BAA in the present case are rare.…”
Section: Editormentioning
confidence: 64%
“…Editor: An infected aortic aneurysm is an uncommon but potentially fatal condition, and endovascular techniques are increasingly being recognized as an alternative to surgery (1,2). Covered endovascular reconstruction of aortic bifurcation (CERAB) is an endovascular technique used in the treatment of chronic occlusive aortoiliac disease (3,4). We modified the CERAB technique to treat a patient with an infected aortic aneurysm.…”
Section: Editormentioning
confidence: 99%